2020
DOI: 10.1097/pec.0000000000002234
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Symptoms of Anxiety Predict Positive Suicide Risk Screening in Adolescents Presenting to the Emergency Department

Abstract: Objective:The objective of this study was to assess whether patient-reported anxiety symptoms are associated with suicide risk in pediatric emergency department (ED) patients. An additional objective was to examine differences between patients presenting for medical/surgical or psychiatric complaints.Methods: Pediatric patients aged 10 to 21 years were recruited from 3 pediatric EDs. Participants completed self-report questionnaires assessing for suicidal ideation and behavior, in addition to questions of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…15 A study of 522 teenage patients admitted to an ED in the United Kingdom found that patients reporting recent feelings of anxiety had more than five times the risk of suicide (OR, 5.18) than those who did not. 16 Emotional stress can lead to substance abuse and depression, which can in turn lead individuals to choose suicide as the last way out. 17 The spread of COVID-19 is related to emotional stress.…”
Section: Sociodemographic and Clinical Characteristicsmentioning
confidence: 99%
“…15 A study of 522 teenage patients admitted to an ED in the United Kingdom found that patients reporting recent feelings of anxiety had more than five times the risk of suicide (OR, 5.18) than those who did not. 16 Emotional stress can lead to substance abuse and depression, which can in turn lead individuals to choose suicide as the last way out. 17 The spread of COVID-19 is related to emotional stress.…”
Section: Sociodemographic and Clinical Characteristicsmentioning
confidence: 99%
“…In studies of patients with all chief complaints (including psychiatric and medical/surgical), the positivity rate ranged from 8% ( 6 ) to 29% ( 47 ). In studies that only included patients with psychiatric chief complaints (or studies that included a breakdown of solely psychiatric presentations), positivity rates ranged from 36% ( 20 ) to 66% ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…A few papers explored the ASQ's effectiveness in screening younger populations, as young as 8 years old ( 6 , 14 , 20 , 22 , 27 ). Those who screen positive on the ASQ tend to be more often female ( 6 , 14 , 20 , 22 , 29 , 42 , 47 ), older ( 14 , 20 , 22 , 29 , 42 ); and, in “all comer” samples, to present with a psychiatric/suicide-related complaint ( 6 , 22 , 43 ). Being Black/African- American was protective in some studies ( 14 , 42 ) and a risk factor in others ( 20 , 22 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations